Analysis of the Role of Learning Facilities in Improving Regular Students' Understanding of Tahsin at SMA Muhammadiyah 2 Medan - Zulpirandi Nainggolan; Zuliana (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2025)
This study aims to analyze the role of learning facilities in improving the understanding of tahsin among regular students at SMA 2 Muhammadiyah Medan. The research employed a descriptive qualitative method with a field study approach. Data collection techniques included observation, interviews, and document analysis. Observations were conducted directly to assess the condition of facilities supporting tahsin, such as classrooms, standardized Qur’anic manuscripts, and learning media. In-depth interviews were carried out with students, tahsin teachers, and school administrators to obtain a comprehensive overview of the effectiveness of the available facilities. Document analysis examined school policies and supporting data related to Qur’anic learning. The findings reveal that SMA 2 Muhammadiyah Medan has provided relatively adequate facilities, including conducive classrooms, the availability of Qur’anic manuscripts, and the use of digital devices in the learning process. These facilities have been proven to support students’ improvement in tajwīd application and correct articulation of letters. Both students and teachers generally expressed positive perceptions of the existing facilities, as students felt it was easier to understand tahsin with the available support. Nevertheless, the study also identified areas for further development, such as the addition of diverse audio-visual media and the enhancement of digital facility utilization to strengthen the effectiveness of the learning process.